How the good guys finally won notes from an impeachment summer - Breslin, Jimmy (New York : Viking Press, 1975)
In the spring of 1974 Jimmy Breslin went to Washington to observe at first hand the inching along of the cumbersome impeachment process of US President Richard Nixon. This book provides a vivid insight into how it came to pass and how the good guys won.
English
Keywords: Nixon, Richard M. -- 1913-1994 -- Impeachment; Nixon, Richard Milhous, -- 1913- -- Destitution, Procédure de; Nixon, Richard Milhous. 1913- -- Impeachment